Anterior and Posterior Leaflets Augmentation to Treat Tricuspid Valve Regurgitation. Issue 5 (4th December 2014) - Quarti, Andrea; Iezzi, Federica; Soura, Elli; Colaneri, Massimo; Pozzi, Marco
ABSTRACT In congenital non‐Ebstein anomalies of the tricuspid valve, the septal leaflet is often involved and tethered. We describe a standardized approach to address septal leaflet tethering by concomitant augmentation of the anterior and posterior leaflets. doi: 10.1111/jocs.12482 (J Card Surg 2015;30:421–423)